2015
DOI: 10.1002/2015jd023132
|View full text |Cite
|
Sign up to set email alerts
|

Lightning strikes to tall objects: A study of wave interactions at the return‐stroke front using a nonlinear transmission line model

Abstract: A theoretical study is presented to investigate lightning strikes to towers, with focus on wave interactions occurring at the return-stroke front due to the arrival of current pulses that propagate upward on the channel after being transmitted from the tower. The lightning channel is represented as a transmission line including corona and nonlinear losses. Analyses for the hypothetical case of a lossless channel considering matched tower and channel impedances show that the arrival of current pulses at the upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…During the past decades, much attention has been paid to the modeling of return‐strokes to tall strike objects (e.g., Baba & Rakov, 2005a, 2005b, 2007; Bermudez et al., 2003, 2005; Pavanello, Rachidi, Rubinstein, et al., 2007; Pavanello, Rachidi, Janischewskyj, et al., 2007; Rachidi et al., 2001, 2002). Other studies have also taken into account the grounding conditions (Petrache et al., 2005), the presence of an upward‐connecting leader (e.g., Mosaddeghi et al., 2011; Shostak et al., 2000), and wave interactions at the return‐stroke wavefront (De Conti et al., 2015; Mosaddeghi et al., 2011;Shoory et al., 2011). Nonuniform, multiple‐section modeling of the struck tower was considered in Boev and Janischewskyj (2011), Rahimian and Hussein (2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, much attention has been paid to the modeling of return‐strokes to tall strike objects (e.g., Baba & Rakov, 2005a, 2005b, 2007; Bermudez et al., 2003, 2005; Pavanello, Rachidi, Rubinstein, et al., 2007; Pavanello, Rachidi, Janischewskyj, et al., 2007; Rachidi et al., 2001, 2002). Other studies have also taken into account the grounding conditions (Petrache et al., 2005), the presence of an upward‐connecting leader (e.g., Mosaddeghi et al., 2011; Shostak et al., 2000), and wave interactions at the return‐stroke wavefront (De Conti et al., 2015; Mosaddeghi et al., 2011;Shoory et al., 2011). Nonuniform, multiple‐section modeling of the struck tower was considered in Boev and Janischewskyj (2011), Rahimian and Hussein (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported directly measured lightning currents and associated electric fields (e.g., Pavanello et al, 2007;Pichler et al, 2010;Saito et al, 2015;. Modeling attempts with varying degree of success were reported by Pavanello et al (2007), Kordi et al (2003), Saito et al (2015), , and Zhu et al (2018). As of today, no one formulated the problem in the framework of 3-D finite difference time domain (FDTD) method.…”
Section: Introductionmentioning
confidence: 99%